Customer Relationship Management (CRM) Integration in E-Commerce: Impacts on Consumer Loyalty and Retention - Pratama, Denny; Wulandari, Indah; Hidayat, Fajar; Lim, Catherine (Lembaga Publikasi Ilmiah Nusantara, 2025)
This study examines the influence of Customer Relationship Management (CRM) integration on consumer loyalty and retention within the e-commerce sector. As online competition intensifies, e-commerce businesses must develop personalized, consistent, and value-driven customer interactions. Utilizing a quantitative approach, data were collected through an online survey of 300 e-commerce users in Indonesia. The study employs Structural Equation Modeling (SEM) to analyze the relationship between CRM dimensions customer database quality, service responsiveness, personalization, and multichannel integration and their impact on consumer loyalty and retention. Findings reveal that CRM integration significantly enhances customer loyalty, which in turn leads to stronger retention. Personalization and service responsiveness emerged as the strongest predictors. The study highlights the strategic role of CRM systems in fostering long-term consumer engagement and provides practical recommendations for e-commerce firms aiming to build sustainable customer relationships.